Therapeutic modulation of gene expression in the disease state: Treatment strategies and approaches for the development of next-generation of the epigenetic drugs - Rittiner, Joseph; Cumaran, Mohanapriya; Malhotra, Sahil; Kantor, Boris (Frontiers in Bioengineering and Biotechnology, 2022)
Epigenetic dysregulation is an important determinant of many pathological conditions and diseases. Designer molecules that can specifically target endogenous DNA sequences provide a means to therapeutically modulate gene function. The prokaryote-derived CRISPR/Cas editing systems have transformed our ability to manipulate the expression program of genes through specific DNA and RNA targeting in living cells and tissues. The simplicity, utility, and robustness of this technology have revolutionized epigenome editing for research and translational medicine. Initial success has inspired efforts to discover new systems for targeting and manipulating nucleic acids on the epigenetic level. The evolution of nuclease-inactive and RNA-targeting Cas proteins fused to a plethora of effector proteins to regulate gene expression, epigenetic modifications and chromatin interactions opened up an unprecedented level of possibilities for the development of “next-generation” gene therapy therapeutics. The rational design and construction of different types of designer molecules paired with viral-mediated gene-to-cell transfers, specifically using lentiviral vectors (LVs) and adeno-associated vectors (AAVs) are reviewed in this paper. Furthermore, we explore and discuss the potential of these molecules as therapeutic modulators of endogenous gene function, focusing on modulation by stable gene modification and by regulation of gene transcription. Notwithstanding the speedy progress of CRISPR/Cas-based gene therapy products, multiple challenges outlined by undesirable off-target effects, oncogenicity and other virus-induced toxicities could derail the successful translation of these new modalities. Here, we review how CRISPR/Cas—based gene therapy is translated from research-grade technological system to therapeutic modality, paying particular attention to the therapeutic flow from engineering sophisticated genome and epigenome-editing transgenes to delivery vehicles throughout efficient and safe manufacturing and administration of the gene therapy regimens. In addition, the potential solutions to some of the obstacles facing successful CRISPR/Cas utility in the clinical research are discussed in this review. We believe, that circumventing these challenges will be essential for advancing CRISPR/Cas-based tools towards clinical use in gene and cell therapies.